Biocatalysis : - Grunwald, Peter (Imperial College Press, 2009)
Contents: Introduction; History of Biocatalysis; Classification of Enzymes; Non-protein Groups in Biocatalysis; Introduction into Kinetics; Enzyme Kinetics; Mechanisms in Enzymatic Catalysis and Enzyme Models; Synthesis of Peptide Antibiotics; Immobilization Biocatalysts; Structure, Function, and Application of Enzymes; Enzymes in Non-conventional Media; Methods to Improve Biocatalysts; Metabolic Pathway Engineering; Catalytic Antibodies; Nucleic Acids as Catalysts; Use of Enzymes in Industry; White Biotechnology.